Penetapan Kadar Tanin Pada Teh Celup Yang Beredar Dipasaran Secara Spektrofotometri UV-Vis - Anzharni Fajrina; Junuarty Jubahar; Stevani Sabirin (Jurnal Farmasi Higea, 2016)
The assay was conducted on tannins tea bag on the market Ultraviolet Visible spectrophotometry method. The samples used was tea bags with brand TM, TS, TP, TR, TJ and pure tea as a comparison. Tea powder sample were extracted using 70 % ethanol.to determine the type and content of tannin used catechins. On the quantitative test is obtained maximum wavelength of 222.00 nm catechins. The calibration curve cathecin is y = 0.04943x + 0.06692. with the value count r = 0.9995. The result showed levels of tannins in tea bag brand TM (0.00919 %), TS (0.00882 %), TP (0.00863 %), TR (0.00766 %), TJ (0.01184 %) and pure tea (0.01207 %). The research shows. kruscal wallis test results showed significant difference (P<0,05) between all brands of used tea bag with pure tea and significant difference between each tea bag.